1996
DOI: 10.1111/j.1600-0773.1996.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a‐Trinositol on Cholera Toxin‐Induced Hypersecretion and Morphological Changes in Pig Jejunum

Abstract: alpha-Trinositol (D-myo-inositol 1,2,6-trisphosphate, PP56) is a novel antiinflammatory drug. This study elucidates the effect of intravenous alpha-trinositol on basal and acute fluid transport and morphological changes following cholera toxin administration in pig jejunum in vivo. Using isolated jejunal tied-off loops, the fluid hypersecretory (accumulation) effect of different doses of cholera toxin was studied in pigs treated intravenously with saline added different doses (0, 4, 8, 16 and 32 mg x kg-1 x hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Both 5-HT and PGE2 induce secretion by direct stimulation of the enterocytes [35] and by activating the ENS [36]. Furthermore, PGE2 suppresses ileal Na+ and water absorption [37, 381. No intramural fluid accumulation was observed after CT stimulation, consistent with CT inducing secretion without histological changes [30].…”
Section: Discussionsupporting
confidence: 67%
“…Both 5-HT and PGE2 induce secretion by direct stimulation of the enterocytes [35] and by activating the ENS [36]. Furthermore, PGE2 suppresses ileal Na+ and water absorption [37, 381. No intramural fluid accumulation was observed after CT stimulation, consistent with CT inducing secretion without histological changes [30].…”
Section: Discussionsupporting
confidence: 67%
“…Previous data have shown that a-trinositol was able to inhibit cholera toxin (CT)-induced intestinal secretion in the pig and rat jejunum in vivo (Nellgå rd et al 1992b, Hansen et al 1996, Tindholdt et al 1997. As the inflammatory changes induced in the gut wall by CT (Ohishi & Odagiri 1984) are far less pronounced than changes caused by E. coli heat-stable toxin (Salvemini et al 1999, Allcock et al 2001, the authors suggested another mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a-trinositol on fluid transport in the small intestine were investigated in a number of studies showing that the compound was able to induce a dosedependent inhibition of cholera secretion in the pig and rat jejunum in vivo (Nellgå rd et al 1992b, Hansen et al 1996, Tindholdt et al 1997. In a recent study, a-trinositol was also shown to inhibit the fluid losses induced by obstruction of the jejunum in rats in vivo at a dose of 60 mg kg )1 h )1 parallel to a significant inhibition of oedema formation in the obstructed gut (Lahti et al 2002).…”
mentioning
confidence: 99%
“…The secretory responses to CT and ST in the small intestine are often compared because they both induce fluid and electrolyte secretion (Klimpel et al., 1995; Grøndahl et al., 1998). The major difference in the pathophysiology between CT and ST is that CT induces no inflammatory or morphological changes (Klimpel et al., 1995; Hansen et al., 1996). This complicates a direct comparison of the potency of CT and ST.…”
Section: Discussionmentioning
confidence: 99%